Physicochemical Analysis of the Polydimethylsiloxane Interlayer Influence on a Hydroxyapatite Doped with Silver Coating. (28th May 2015) - Popa, C. L.; Groza, A.; Chapon, P.; Ciobanu, C. S.; Ghita, R. V.; Trusca, R.; Ganciu, M.; Predoi, D.
Abstract : We investigate by different complementary methods the processes occurring when a polydimethylsiloxane film is used as interlayer for a silver doped hydroxyapatite coating. The X-ray diffraction and Fourier Transform Infrared Spectroscopy measurements show that the hydroxyapatite doped with silver is in a crystalline form and someSiO 4 4 - ions formation takes place at the surface and in the bulk of the new hydroxyapatite doped with silver/polydimethylsiloxane composite layer. The possibility ofSiO 4 4 - ions incorporation in the structure of silver doped hydroxyapatite by the mechanism ofSiO 4 4 - /PO 4 3 - ions substitution is analysed. The new formed silver doped hydroxyapatite/polydimethylsiloxane composite layer is compact, homogeneous, with no cracks as it was shown by Scanning Electron Microscopy and Glow Discharge Optical Emission Spectrometry.